Pengembangan Model Latihan Long Pass Control dalam Permainan Sepakbola untuk Siswa Usia 14-16 Tahun di Sekolah Sepakbola Mitra Jaya Soccer Kota Malang - Mahbubi, Rizalul; Adi, Sapto (Performance, 2017)
This study aims to develop a model of long pass control kicking practice. This study uses a study design and development of Borg and Gall. The subjects used were students aged 14-16 years in the school of football Mitra Jaya Soccer, Malang. Mechanical analysis of this research is a descriptive percentage, i.e for processing quantitative and qualitative data, the instrument used was a questionnaire. This research has been through some expert tests. The football expert test results which is obtained a score of 91,6%, soccer coaching expert test obtained a score of 81% and 75% media expert test, after several expert test and then implement a test conducted by a small group of eight students and earn a score of 88,73%, then carry out trials which is conducted by a large group of 22 students and earn a score of 88,75%. From the results of the data analysis to determine the level of validity of the product, so the product development model of practice for a long pass control which is packaged in the form of video is declared fit for use as a model practice for students aged 14-16 years in the School of Mitra Jaya Soccer Malang. Keywords: practice model long pass control, soccer gameAbstrak: Penelitian ini bertujuan untuk mengembangkan model latihan menendang long pass control. Penelitian ini menggunakan rancangan penelitian dan pengembangan dari Borg dan Gall. Subjek yang digunakan adalah siswa usia 14-16 tahun di Sekolah Sepakbola Mitra Jaya Soccer Kota Malang. Teknik analisis penelitian ini adalah deskriptif persentase, yaitu untuk mengolah data kuantitatif dan kualitatif, instrumen yang digunakan adalah angket kuisioner. Penelitian ini telah melalui beberapa uji ahli. Hasil uji ahli sepakbola memperoleh skor 91,6 %, uji ahli kepelatihan sepakbola memperoleh skor 81% dan uji ahli media 75%, setelah melalui beberapa uji ahli kemudian melaksanakan uji coba kelompok kecil yang dilakukan oleh delapan siswa dan memperoleh skor 88,73%, kemudian melaksanakan uji coba kelompok besar yang dilakukan oleh 22 siswa dan memperoleh skor 88,75%. Dari hasil data tersebut dilakukan analisis data untuk mengetahui tingkat validitas produk, sehingga produk pengembangan model latihan long pass control yang dikemas dalam bentuk video ini dinyatakan layak digunakan sebagai model latihan untuk siswa usia 14-16 tahun di Sekolah Sepakbola Mitra Jaya Soccer Kota Malang.Kata kunci: model latihan long pass control, permainan sepakbola